واقع تصورات طلاب المرحلة المتوسطة نحو استخدام برنامج دروب الرياضيات للتعلم الإلكتروني أثناء أزمة كورونا Covid 19 - الرويلي، عايد بن عايض (جامعة حائل, 2023)
هدفت الدراسة إلى التعرف على واقع التصورات لدى طلاب المرحلة المتوسطة لمقرر الرياضيات نحو استخدام برنامج التعلم الإلكتروني "برنامج دروب الرياضيات" أثناء أزمة كورونا Covid-19، حيث استخدم الباحث المنهج الوصفي التحليلي لمجموعة من الطلاب مكونة من 95 طالب، وتم إعداد أدوات الدراسة اللازمة من أجل التأكد من صدق وثبات أدوات القياس والمعالجة، حيث أثبتت النتائج أن تصورات الطلاب لاستخدام برنامج دروب الرياضيات كأحد برامج التعلم الإلكتروني أثناء أزمة كورونا Covid-19 قد سد الفجوة بدرجة عالية في العملية التعليمية لدى طلاب المرحلة المتوسطة، وأوصت الدراسة بضرورة تبني برامج التعلم الإلكترونية في التعلم لطلاب التعليم العام، مع السعي نحو نشر ثقافة التدريس للمعلمين عبر البرامج التعليمية، وتنظيم دورات تدريبية وورش عمل للتدريب على استخدام برامج التعلم الإلكترونية لكل من الطلاب والمعلمين مع ضرورة تبني استخدام البرامج التعليمية الإلكترونية بشكل واسع في عملية التدريس. The study aimed to realize the impact of learning motivation among students of general education for the mathematics course in the city of Arar towards the use of the e-learning program "Destination Math Program" during the Corona Covid-19 pandemic, where the researcher was keen to apply the survey method to a sample of students consisting of 95 students, and a sample of 95 students was also prepared. The study toolkit to ensure the validity and reliability of the measurement and treatment tools, as the study found that the students’ learning motivation towards using the Destination Math Program during the Corona Covid-19 crisis has addressed the gap in a high degree in the educational process among middle school students, and the study recommended the need to adopt electronic learning programs in learning For public education students, spreading the culture of teaching for teachers through educational programs, and organizing training courses and workshops for training on the use of electronic learning programs for both students and teachers, with the need for the General Education Department to adopt the use of electronic educational programs on a large scale.
Keywords: جائحة كورونا "كوفيد-19" -- العملية التعليمية -- يرامج التعليم الإلكتروني -- إدارة الحاسوب